Формирование морфологических структур сеянцев Hemerocallis hybrida Hort. ′Radiant Greetings′ в процессе онтогенеза в Донбассе - Крохмаль, И.И. (Промышленная ботаника, 2004)
Peculiarities of forming of morphologic structures of seedlings of ‘Radiant Greetings‘ variety of Hemerocallis hybrida Hort. in the process of ontogenetic development have been studied. 2 periods: latenal, virginal and 4 age states of virginal period have been distinguished: sprouts, juvenile, immature, virginal. Their terms and duration under the new conditions have been defined. It has been determined that root system is equally allocated at the end of the first year of plant development, it is of fibrillose type, consists of 5 – 10 adventitios roots, with the development of a large number of resorpting roots of the second and third order. In the second year of plants life, a new cycle of adventitious roots located above the old ones is formed; rhizome grows upwards.